Vestibular evoked myogenic potential may predict the hearing recovery in patients with unilateral idiopathic sudden sensorineural hearing loss - Liang, Min; Wu, Hui; Chen, Jianyong; Zhang, Qin; Li, Shuna; Zheng, Guiliang; He, Jingchun; Chen, Xiangping; Duan, Maoli; Yang, Jun; Jin, Yulian (Frontiers in Neurology, 2022)
Objective: This study is aimed at studying the association between vestibular function and prognosis in patients with unilateral idiopathic sudden sensorineural hearing loss (UISSNHL). Design: A retrospective analysis of 64 patients with UISSNHL was performed. Pure tone audiometry and speech audiometry, vestibular function tests for otoliths and semicircular canal were performed to assess the influence of vestibular functional status on the outcome of UISSNHL patients. Results: Patients with abnormal cervical vestibular evoked myogenic potential (cVEMP) or ocular vestibular evoked myogenic potential (oVEMP) responded less favorably to treatments. In the ineffective group, cVEMP was normal in 4 patients (6.3%) and oVEMPs in 3 (4.7%), while cVEMP was abnormal in 32 patients (50.0%) and oVEMP in 33 (51.6%). Better hearing recovery occurred in those with normal cVEMP (33.76 (15.07) dB HL improvement) or oVEMP (32.55 (19.56) dB HL improvement) but not in those with normal caloric test. Patients with abnormalities in both cVEMP and oVEMP were less responsive to treatment, who also had worse hearing recovery than those with normal results in only one of the two tests. Conclusions: Abnormal oVEMP and/or cVEMP results indicate poor auditory outcomes in patients with UISSNHL. Patients with UISSNHL who have impaired otolith organ function are likely to have a larger and more severe pathological change in their inner ear.